A square peg in a round hole inclusion for every child - Tallent, Linda; Thompson, Jean (Featherstone Education, 2011)
This book identifies the barriers that children with a wide range of different additional needs experience in school. It provides case studies of each of the major conditions, describes the behaviour of the child involved and the process of diagnosis, concluding with practical strategies on how to help these children become successful learners.